Peningkatan Kemampuan Menulis Narasi dengan Menggunakan Media Gambar Berseri pada Siswa Kelas III di SDN Gedong 03 Pagi - Eva Oktaviana (LPPM STKIP Kusuma Negara, 2017)
The purpose of this study was to determine how the application of media Gambar Berseri, and improve students’ ability in writing narrative. This research conducted to the third-grade of SDN 03 Gedong Pagi Jakarta Timur, and the total numbers of the students are 35. Kemmis Taggart, who performed during the second cycle. Each cycle consists of planning, implementation of action, observation and reflection action. The process of collecting data through narrative writing skills test using the observation sheet activities of teachers and students, field notes, and documentation of results. The results of observation showed that there was an increase in students’ ability in writing narrative text through Media Gambar Berseri. Student in the first cycle, who get scored above 70 to 23 people, or about 65, 71% of students who completed, an increase in cycle II students who get scored in the top 70, there are 31 approximately 88.57% of the students who completed. Activities of teachers and students based these media that reach out 80% in the second cycle. The implications of the study identify that the using of media Gambar Berseri makes student responsibility, actively, and cooperate in the study. Teachers can develop methods innovatively based students’ need, so that the learning process becomes dynamic and meaningful.